Eleonora Pasotti, Resisting Redevelopment. Protest in Aspiring Global Cities, Cambridge, Cambridge University Press, 2020 - Pinson, Gilles (PARTECIPAZIONE E CONFLITTO, 2023)
For Book Reviews Abstract is not mandatory